Comparison of different sets of immunological tests to identify treatable immunodeficiencies in adult bronchiectasis patients. Issue 1 (28th March 2022) - Aliberti, Stefano; Amati, Francesco; Gramegna, Andrea; Vigone, Barbara; Oriano, Martina; Sotgiu, Giovanni; Mantero, Marco; Simonetta, Edoardo; Saderi, Laura; Stainer, Anna; Tammaro, Serena; Marchisio, Paola; et al.
Background: The reported prevalence of immunodeficiencies in bronchiectasis patients is variable depending on the frequency and extent of immunological tests performed. European Respiratory Society guidelines recommend a minimum bundle of tests. Broadening the spectrum of immunological tests could increase the number of patients diagnosed with an immunodeficiency and those who could receive specific therapy. The primary objective of the present study was to assess the performance of different sets of immunological tests in diagnosing any, primary, secondary or treatable immunodeficiencies in adults with bronchiectasis. Methods: An observational, cross-sectional study was conducted at the Bronchiectasis Program of the Policlinico University Hospital in Milan, Italy, from September 2016 to June 2019. Adult outpatients with a clinical and radiological diagnosis of bronchiectasis underwent the same immunological screening during the first visit when clinically stable consisting of: complete blood count; immunoglobulin (Ig) subclass tests for IgA, IgG, IgM and IgG; total IgE; lymphocyte subsets; and HIV antibodies. The primary endpoint was the prevalence of patients with any immunodeficiencies using five different sets of immunological tests. Results: A total of 401 bronchiectasis patients underwent the immunological screening. A significantly different prevalence of bronchiectasis patients diagnosed with any, primary or secondary immunodeficiencies was found across different bundles. 44.6% of bronchiectasis patients had a diagnosis of immunodeficiency when IgG subclasses and lymphocyte subsets were added to the minimum bundle suggested by the guidelines. Conclusion: A four-fold increase in the diagnosis of immunodeficiencies can be found in adults with bronchiectasis when IgG subclasses and lymphocyte subsets are added to the bundle of tests recommended by guidelines. A four-fold increase in the diagnosis of immunodeficiencies is found in adults with bronchiectasis when IgG subclasses and lymphocyte subsets are added to the bundle of tests recommended by @EuroRespSoc guidelines https://bit.ly/2ZVd2aO